Carbon emission reduction effects in Yangtze River Delta from the dual perspectives of forest resource endowment and low-carbon pilot policy in the digital age - Zhang, Qian; Wang, Rong (Frontiers in Forests and Global Change, 2023)
Although Chinese society has transformed into the digital age, carbon peaking and neutrality are still important starting points for implementing the national strategy of green and low-carbon integrated growth in the Yangtze River Delta (YRD) of China. With data from 41 cities in YRD from 2005 to 2019, this paper empirically analyzes the carbon emission reduction effects from dual perspectives of forest resource endowment and low-carbon pilot policy in the digital age. The findings include: (1) Forest resources are indeed conducive to reducing carbon emissions. However, when considering the carbon sequestration effect of forests, a nonlinear U-shaped relationship exists between forest resource abundance and net carbon emissions per GDP. (2) Low-carbon city pilot policies are effective in reducing carbon emissions. (3) Low-carbon pilot policies perform better in smart cities, resource-based cities, and cities with abundant forest resources, showing significant heterogeneity. Forests can be relied on to assist in carbon emission reduction in the short term, but in the long term, a forest ecosystem with biodiversity is needed to achieve low-carbon sustainable development. This article provides some experience and references for building green and carbon-neutral cities for YRD in the digital age.